FRAMING DALAM PEMBENTUKAN KONSTRUKSI SOSIAL KORBAN CYBERBULLYING: KASUS BU PRANI DI FILM BUDI PEKERTI - Shalya Cahya Haliza (Prodi Sosiologi FISIP UPR, 2025)
This research aims to analyze the framing employed in the film Budi Pekerti which depicts a case of cyberbullying against Bu Prani, a guidance counselor who becomes a victim of social stigma due to the spread of a viral video. The film vividly demonstrates how society often forms hasty conclusions without understanding the actual context, resulting in various harmful negative reactions towards the victim. This qualitative study utilizes a data collection technique involving direct observation of scenes in the film, documentation, and a literature review focusing on framing theory and social construction. The findings indicate that biased framing can create public perceptions that are inconsistent with reality, damage an individual's reputation, and reinforce social stigma against victims. In Bu Prani's case, the narrative presented through social media in the film demonstrates how public opinion is shaped by disseminated information, even if it is not always accurate or complete. This research concludes that by enhancing media literacy, the public can become more critical in responding to the information they receive. This not only helps reduce the negative impacts of unfair framing but also promotes the emergence of more positive and empathetic narratives towards victims of cyberbullying.